2020
DOI: 10.1055/s-0040-1712544
|View full text |Cite
|
Sign up to set email alerts
|

Convulsive Status Epilepticus in Children: A Prospective Observational Study from India

Abstract: Convulsive status epilepticus (CSE) is one of the commonest and life threatening pediatric neurological emergencies. Only few studies on pediatric status epilepticus (SE) are available from the Indian subcontinent. The aim was to study the etiology and immediate outcome of CSE in children getting admitted in pediatric emergency during the study period and to study association of various clinical presentations with immediate outcome. A prospective observational study was conducted in tertiary care institute of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In our study, the mean age of the children was 4.9 years and 55.4% were male patients. The increased prevalence of CSE in children <5 years of age has been reported in various studies conducted across India (Chin, 8 Bergamo et al, 9 and Admuthe et al, 10 in their study have also observed the mean age for the CSE 4.5 years and findings are consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the mean age of the children was 4.9 years and 55.4% were male patients. The increased prevalence of CSE in children <5 years of age has been reported in various studies conducted across India (Chin, 8 Bergamo et al, 9 and Admuthe et al, 10 in their study have also observed the mean age for the CSE 4.5 years and findings are consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar risk factors were found in other studies. 10,[15][16][17] In our study, the outcome was good among cases who had traveled <10 km and was very high among 24 children who had traveled more than 40 km. The study revealed that the lower the distance to the treating hospital, the better the outcome and vice voce.…”
Section: Discussionmentioning
confidence: 42%
“…A previous study from this center also had higher mortality in females. 5 Two out of three deaths during follow-up were due to seizures and one due to aspiration. All of them were in a persistent vegetative state at the time of discharge.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4] The mortality at discharge in resource-poor countries ranges between 10 and 30%, whereas in developed nations it is 2 to 7%. [5][6][7][8] In a review by Sculier et al, long-term mortality after status epilepticus (SE) was noticed up to 20% in children and 55% in adults; in older studies mortality was higher whereas in newer studies it was < 5%. 4 Pujar et al reported 11% case fatality rate on 8-year follow-up of childhood CSE.…”
Section: Introductionmentioning
confidence: 99%